Relationship Between Knowledge Levels About The Impact Of Smoking On Family Health And Smoking Behavior In The Community Of Dusun E Gampong Uteunkot - Angga Wibatsu Karim; Cut Khairunnisa; Nina Herlina (Faculty of Medicine University of Malikussaleh, 2022)
Abstract: Smoking behaviour is a problem and a national priority in improving the health status of the Indonesian people because it involves various aspects of problems in life, namely economic, socio-political and especially health aspects. This can be seen in everyday life such as at home, on public transportation or in the office, almost every time people are found and found smoking. Smoking behaviour is not only found among adults but can also be found among adolescents. Although information and knowledge about the impact of smoking on the health of smokers as well as on the surrounding environment, especially families, is widely conveyed, this smoking behaviour is still carried out. Purpose: The purpose of this study was to determine the relationship between the level of knowledge about the impact of smoking on family health and smoking behaviour in the Dusun E Gampong Uteunkot community Patients and methods: This study is an analytic observational of 235 samples aged > 17 years which were taken by purposive sampling. Measurements were made using a questionnaire consisting of knowledge about the impact of smoking on the health of oneself and one's family and smoking behaviour. Results: The results of this study indicate that the majority of respondents who have a good level of knowledge about non-smoking behaviour are 36.1%. Data analysis using Chi-square. The results of statistical analysis showed p value <0.05. Conclusion: The conclusion of this study is that there is a relationship between the level of knowledge about the impact of smoking on family health and smoking behaviour in the Dusun E Gampong Uteunkot community.